The Arabidopsis szl1 Mutant Reveals a Critical Role of β-Carotene in Photosystem I Photoprotection(1)([C])([W]) - Cazzaniga, Stefano (American Society of Plant Biologists, 2012)
Carotenes and their oxygenated derivatives, the xanthophylls, are structural determinants in both photosystems (PS) I and II. They bind and stabilize photosynthetic complexes, increase the light-harvesting capacity of chlorophyll-binding proteins, and have a major role in chloroplast photoprotection. Localization of carotenoid species within each PS is highly conserved: Core complexes bind carotenes, whereas peripheral light-harvesting systems bind xanthophylls. The specific functional role of each xanthophyll species has been recently described by genetic dissection, however the in vivo role of carotenes has not been similarly defined. Here, we have analyzed the function of carotenes in photosynthesis and photoprotection, distinct from that of xanthophylls, by characterizing the suppressor of zeaxanthin-less (szl) mutant of Arabidopsis (Arabidopsis thaliana) which, due to the decreased activity of the lycopene-β-cyclase, shows a lower carotene content than wild-type plants. When grown at room temperature, mutant plants showed a lower content in PSI light-harvesting complex I complex than the wild type, and a reduced capacity for chlorophyll fluorescence quenching, the rapidly reversible component of nonphotochemical quenching. When exposed to high light at chilling temperature, szl1 plants showed stronger photoxidation than wild-type plants. Both PSI and PSII from szl1 were similarly depleted in carotenes and yet PSI activity was more sensitive to light stress than PSII as shown by the stronger photoinhibition of PSI and increased rate of singlet oxygen release from isolated PSI light-harvesting complex I complexes of szl1 compared with the wild type. We conclude that carotene depletion in the core complexes impairs photoprotection of both PS under high light at chilling temperature, with PSI being far more affected than PSII.